“SPECTACLE GALLERY” MUARA BARU - Wendy Wennas; F. Tatang H. Pangestu2 (Jurusan Arsitektur dan Perencanaan, 2022)
The development of the city of Jakarta began in the seafront area, which later developed into the city center as a port. For example, the Sunda Kelapa Harbor, has been used since the time of Tarumanegara and is often contested to control trade. Now coastal areas are starting to be abandoned because they continue to experience disasters. Close to the port, in the Muara Baru area, there is a mosque that has sunk due to an old embankment that collapsed by the tidal flood and is now a blind witness that Jakarta will sink. In the past, the area was active; there were many fishing activities and routine recitations. Now the area is limited by a new 4 meter high embankment and the availability of facilities and infrastructure is also insufficient. Because of this, the identity of the area becomes negative and continues to experience physical, social, and mental degradation. So the aim of this project is to provide awareness and innovation to the issue, using the concept of